A new affordable flow cytometry based method to measure HIV-1 viral load (2009)
Most commercially available assays for diagnosis of HIV infection have shown shortcomings in the detection and quantification of rare genotypes of the virus. Most of the assays do not detect subtype O (outlier) and/or N (nonmajor, nonoutlier) or new circulating recombinant forms (CRFs), which are becoming more important in sub-Saharan Africa. Furthermore, the commonly available tests require costly measuring devices and expensive test kits, which are not easily affordable for developing countries. This study was designed to explore solutions to the problem of viral load assays in developing countries. Two forward primers, digoxygenin (DIG) and dinitrophenol (DNP) labeled, and one biotin (BIO) labeled reverse primer were used to amplify both, the HIV-1-5'LTR (long terminal repeat) region and an internal standard sequence. The two polymerase chain reaction (PCR)-products were captured by anti-DIG and anti-DNP antibody coated microparticles. Flow cytometric analyses were carried out after labeling with streptavidin-R-phycoerythrine. The primer system used recognized all HIV-1 subtypes. A coamplified internal standard warranted the functionality of the PCR and allows reproducible viral load measurements. Two drawbacks of current viral load measurements are overcome by the flow cytometry based test described hereof. First, all known worldwide relevant HIV-1 subtypes including subtypes O, N, and new CRFs are quantifiable with high sensitivity (50 to >1 x 10(6) copies per PCR). Second, the cost per test can be reduced to less than 12 US$ instead of the current 50-100 US$. Additionally, the test described in this report offers the possibility to perform complete monitoring program (CD4 T-cell count, CD4% and viral load) for the first time, with the same device for HIV-infected persons.